miR-21 mimic blocks obesity in mice: A novel therapeutic option. - Lhamyani, Said; Gentile, Adriana Mariel; Giráldez-Pérez, Rosa María; Feijóo Cuaresma, Mónica; Romero-Zerbo, Silvana Yanina; Clemente-Postigo, María Mercedes; Zayed, Hatem; Oliva-Olivera, Wilfredo; Bermúdez-Silva, Francisco Javier; Salas-Millán, Manuel Julián; López-Gómez, Carlos; Hmadcha, Abdelkrim; et al. (Cell Press, 2021)
MicroRNAs (miRNAs) are promising drug targets for obesity and metabolic disorders. Recently, miRNA mimics are providing a unique mechanism of action that guides the process for drug development and sets out the context of their therapeutic application. miRNA (miR)-21 expression in white adipose tissue (WAT) has been associated with obesity. We aimed to analyze miR-21 expression levels in relation to diabetes and obesity to determine the effect that miR-21 mimic has on processes involved in WAT functionality, to dissect the underlying molecular mechanisms, and to study the potential therapeutic application of the miR-21 mimic against obesity. We found higher miR-21 levels in WAT from non-diabetic obese compared to normoweight humans and mice. Moreover, in 3T3-L1 adipocytes, miR-21 mimic affect genes involved in WAT functionality regulation and significantly increase the expression of genes involved in browning and thermogenesis. Interestingly, in vivo treatment with the miR-21 mimic blocked weight gain induced by a high-fat diet in obese mice, without modifying food intake or physical activity. This was associated with metabolic enhancement, WAT browning, and brown adipose tissue (AT) thermogenic programming through vascular endothelial growth factor A (VEGF-A), p53, and transforming growth factor β1 (TGF-β1) signaling pathways. Our findings suggest that miR-21 mimic-based therapy may provide a new opportunity to therapeutically manage obesity and consequently, its associated alterations.
Keywords: Obesidad; Metabolismo - Alteraciones; Tejido adiposo; Diabetes; TMEM26; Adipose tissue; Brown adipose tissue; Browning; Diabetes; Metabolism; miR-21; Obesity; Thermogenesis; Uncoupling protein 1